Troubled Waters: Navigating Unintended Consequences of Health Information Technology - Lehmann, C. U.; Séroussi, B.; Jaulent, M.-C. (Yearbook of Medical Informatics, 2016)
Objectives: To provide an introduction to the 2016 IMIA Yearbook of Medical Informatics by the editors.Methods: We present a brief overview of the 2016 special topic “Unintended consequences of Health IT: new problems, new solutions”, we review our choice of special topic section editors, and discuss the transitions in the editorial team for next year.Results: This edition of the Yearbook acknowledges the fact that implementation and use of Health Information Technology (HIT) may result in unintended consequences, which may lead to both adverse and sometimes beneficial outcomes. However to date, in the literature, undesired outcomes are emphasized with a focus on the complex causes and the many sources that may generate them. The growing awareness of the importance of HIT’s unintended consequences and their increasing documentation reflect a wider acceptance of HIT by users (more use generating more consequences) and and a new type of users (a shift from early adopters to late adopters and laggards), whith great expectations regarding the improvement of care quality through HIT solutions. Different points of view on new problems and new solutions of unintended consequences of Health IT are presented through the keynote paper, survey papers, and the working group contributions.Conclusions: The regular 2016 issue of the IMIA yearbook focuses on new unintended consequences of Health IT – brought on by wider adoption and different types of users as well as solutions to addressing them.
Keywords: Editorial; 2016 IMIA Yearbook of Medical Informatics; Unintended consequences of Health IT; IMIA and its societies